Stigma Towards People with Schizophrenia Among the Health Study Students: Faculty of Medicine, Faculty of Psychology, and Department of Counseling in Jakarta - Shahnaz Alyssa Abidin; Irwanto (The Center for Disability Studies and Services Brawijaya University, 2021)
Stigma and discrimination against persons with mental disorder has been a global issue. The negative impacts of this includes serious barrier to supportive government policies and detrimental effects to the quality of life of the stigmatized persons. Earlier studies suggest that stigma has been observed among professionals such as medical doctors, nurses, and counselors. This research aims to understand how students of related academic fields such as medicine, psychology, and counseling regard persons with schizophrenia as measured by the Bogardus Social Distance Scale. The study was conducted to 230 students studying in health-related fields (Medicine, Psychology, and Counseling students). Analysis of data were conducted with an independent t-test, One-way ANOVA, and Simple Regression techniques. The results show that students from the health-related field have serious issues with stigma. The majority of the students are not willing to include a person with schizophrenia as their family member or caregiver. Students who have had earlier contact them tend to have lower stigma. However, students who have family members with schizophrenia have a higher stigma. The medical students tend to have higher stigma compared to psychology and other students.